Emergency ambulances on the public highway linked with inconvenience and potential danger to road users. Issue 3 (1st May 2003) - Saunders, G; Gough, A
Abstract : Objectives: The main aim was to survey interactions between the public highway users and emergency ambulances using lights and sirens. The objectives were to identify negative and positive experiences, and to assess the frequency and consequences of these events. Methods: Because of a poor response from a random postal pilot, a quota sample of 200 was adopted with a response of 65%. This provided data on demographics, details of previous interactions, and possible third party effects. Participant perception of psychological stress in negative interactions was also recorded. Possible links between the recorded interactions were assessed using the χ 2 tests of association. Results: The passage of an emergency ambulance using lights and sirens caused the public to move from their chosen position in most cases (61%). Horns or sirens were used frequently (86%), but they were not always applied in unison with the warning lights. A significant association was found between the satisfactory handling of events by the ambulance crews and the use of audible warning devices (p<0.001). Twenty per cent of avoidance manoeuvres necessitated reversing, which was associated with a third party affect (p<0.005). Roughly one third of the participants found interactions stressful and felt that the events could have been avoided. Most public road users (91%) believed that they acted in a controlled manner. Conclusions: The findings suggest that most participants had interacted with the emergency ambulances in a positive manner, while a smaller but significant fraction of the public road users found the interactions difficult to handle. A third party effect was identified in avoidance manoeuvres. Further longitudal research with random sampling is recommended.